Emulating a crowded intracellular environment in vitro dramatically improves RT-PCR performance - Lareu, Ricky R.; Harve, K.; Raghunath, M. (Academic Press, 2007)
The polymerase chain reaction’s (PCR) phenomenal success in advancing fields as diverse as Medicine, Agriculture, Conservation, or Paleontology is based on the ability of using isolated prokaryotic thermostable DNA polymerases in vitro to copy DNA irrespective of origin. This process occurs intracellularly and has evolved to function efficiently under crowded conditions, namely in an environment packed with macromolecules. However, current in vitro practice ignores this important biophysical parameter of life. In order to more closely emulate conditions of intracellular biochemistry in vitro we added inert macromolecules into reverse transcription (RT) and PCR. We show dramatic improvements in all parameters of RT-PCR including 8- to 10-fold greater sensitivity, enhanced polymerase processivity, higher specific amplicon yield, greater primer annealing and specificity, and enhanced DNA polymerase thermal stability. The faster and more efficient reaction kinetics was a consequence of the cumulative molecular and thermodynamic effects of the excluded volume effect created by macromolecular crowding.